Adrenocortical carcinoma complicated by renal thrombotic microangiopathy, a case-series - Tristan de Nattes; Lucile Moreau-Grangé; Delphine Vezzosi; Julien Hadoux; Miguel Hie; Dominique Guerrot; Steven Grangé (BMC Nephrology, 2020)
Abstract Background Cancer-related thrombotic microangiopathy (CR-TMA) is a rare entity associated with a dismal prognosis. Usually, CR-TMA is associated with mucin-producing carcinomas among which stomach, breast, prostate, lung and pancreas tumours are the most frequent. Cases presentation We describe for the first time three cases of CR-TMA due to adrenocortical carcinoma (ACC). All of them had mechanical hemolytic anemia and thrombocytopenia without any other identifiable cause. Bicytopenia was diagnosed either simultaneously with ACC or at the time of metastatic evolution. Two patients had acute kidney injury (AKI) with severe pathological findings on kidney biopsy. Despite total adrenalectomy, chemotherapy, and specific treatment of TMA with plasma-exchanges, renal failure and hemolytic anemia remained. The only manifestation of CR-TMA in the third patient was hemolytic anemia, which resolved after surgical removal of ACC. The evolutions in these patients suggests ACC-related TMA may be related to a circulating factor. Conclusions CR-TMAs are rare. Here we describe the first case series of ACC-related TMA, among which two had renal involvement. This entity is associated with dismal renal prognosis despite specific treatment of TMA. According to patients’ evolution, the persistence of TMA may reflect an uncontrolled malignancy.